2014
DOI: 10.1161/hypertensionaha.114.03811
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Sensor Protein Kinase R–Like Endoplasmic Reticulum Kinase (PERK) Protects Against Pressure Overload–Induced Heart Failure and Lung Remodeling

Abstract: Studies have reported that development of congestive heart failure (CHF) is associated with increased endoplasmic reticulum (ER) stress. Double stranded RNA activated protein kinase-like endoplasmic reticulum kinase (PERK) is a major transducer of the ER stress response and directly phosphorylates eIF2α, resulting in translational attenuation. However, the physiological effect of PERK on CHF development is unknown. In order to study the effect of PERK on ventricular structure and function, we generated inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 37 publications
(53 reference statements)
1
71
0
Order By: Relevance
“…TG also triggered the UPR and accumulation of intracellular procollagen in cultured rat cardiac fibroblasts [21]. Furthermore, accumulating in-vivo data from the pressure overload model implicates ER stress as a central player in the development of cardiac hypertrophy [2224]. In this study, we shed light on the temporal relationship between ER stress and LVH, demonstrating that the ER stress response persists up to 4 weeks after TAC.…”
Section: Discussionmentioning
confidence: 63%
“…TG also triggered the UPR and accumulation of intracellular procollagen in cultured rat cardiac fibroblasts [21]. Furthermore, accumulating in-vivo data from the pressure overload model implicates ER stress as a central player in the development of cardiac hypertrophy [2224]. In this study, we shed light on the temporal relationship between ER stress and LVH, demonstrating that the ER stress response persists up to 4 weeks after TAC.…”
Section: Discussionmentioning
confidence: 63%
“…The increased CHOP expression also found in PERK knockout hearts after TAC, confirms that CHOP may contribute to the left ventricular dysfunction by increasing apoptosis. In the same paper [111] the Authors also observed a significant decline of sarcoplasmic reticulum Ca2+ ATPase (Serca2a) expression.…”
Section: Lvh and Hfmentioning
confidence: 77%
“…PERK has recently been demonstrated to protect the heart from pressure overloadinduced congestive HF: in response to chronic TAC, PERK knockout mice exhibited decreased ejection fraction, increased left ventricular fibrosis and enhanced cardiomyocyte apoptosis [111]. The increased CHOP expression also found in PERK knockout hearts after TAC, confirms that CHOP may contribute to the left ventricular dysfunction by increasing apoptosis.…”
Section: Lvh and Hfmentioning
confidence: 79%
“…Increasing proteo toxic stress in experimental animal models by inhibition or knock out of important enzymes involved in PQCoften in mice with transverse aortic binding -implicate the cardiac activation of various signalling pathways associated with progression or attenu ation of heart dis ease. Signalling includes detrimental pathways, such as the calcineurin-NFAT pathway 150 , phosphorylation of eukaryotic translation initiation factor (eIF) 2α 151 , and induction of apoptosis [151][152][153] , but also favourable path ways, such as protection against oxidative stress through upregu lation of catalase 154 , or transcriptional activation of the hexo samine biosynthetic pathway supplying the sub strate for protein glycosylation 150 . Nevertheless, despite disclosure of these pathways, the dominant pathways linking cardio myocyte proteotoxic stress to subsequent cell death and cardiac remodelling in various cardiac conditions are still not well defined.…”
Section: Nature Reviews | Cardiologymentioning
confidence: 99%